New association between Amblyomma parvitarsum (Acari: Ixodidae) and the endemic lizard Liolaemus eleodori (Iguania: Liolaemidae) in Argentina - Castillo, Gabriel Natalio (2019)
Records of lizard parasitizing ticks in Argentina are scarce and incomplete. We recorded a newpopulation of Liolaemus eleodori, a lizard endemic to Argentina, parasitized by the hard tick Amblyomma parvitarsum.Hence, the objective of this study is to report this new association and enhance knowledge about its parasitism onreptiles of Argentina. To do this, we researched ectoparasitic loads. We determined different ecological predictors:intensity, mean intensity and prevalence. Our results provide the first data on the parasitism of nymphal stages on thislizard. We found a tick prevalence of 91.6% and a mean intensity of 2.45. Considering sexes, mean intensity was higherin females than in males. The gular region and lower ventral abdomen were the highest parasitized anatomical regions.This new record of the host-parasite association suggests that this relationship is not accidental, with this lizard speciesbeing central to the tick?s life cycle. Probably, the microhabitat of this lizard species is essential for the tick to reachhigh prevalence. Our study represents an important contribution and provides additional information on parasitism inlizards of Argentina.